Co-creation as a Methodology to Integrate Mental Health and Psychosocial Support and Peacebuilding - Yvonne Sliep; Marian Tankink; Friederike Bubenzer (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
The integration of peacebuilding and mental health and psychosocial support (MHPSS) is a new field that is receiving increased attention from policy makers, local and international civil society organisations and donors. The authors conducted pilot studies in four countries over a 4-year period using a co-creation process. Acknowledging that this is a new body of knowledge that is evolving, participants from diverse professional backgrounds, with varied levels of decision-making power and experience, worked collectively towards a new understanding of integrated, contextually relevant solutions to their respective societal challenges. The co-creation process fosters transformative learning and acknowledges local wisdom and practices as well as existing theories and skills. The process includes exploring the context and current situation of a given country, as well as how participants would like to see integration unfold in the short and long term, acknowledging that integration can take on many forms. Fundamentally, co-creation encourages the development of a shared MHPSS and peacebuilding language, promoting mutual understanding across different fields and generating more holistic interventions. The facilitators play a pivotal role, not as experts, but as co-learners, guiding the co-creation journey in a safe, structured environment. Co-creation processes work best when applied as a phased approach over a longer period of time.